Masks for at-risk population: nursing promoting biosafety in pandemic times - Patricia Abrahão-Curvo; Karina Dal Sasso Mendes; Angelina Lettiere-Viana; Maria Cândida de Carvalho Furtado; Thatiana Delatorre; Susana Inés Segura-Muñoz (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To describe a proposal for making and distributing masks for population in risk, with guidance on the stages of making them and the care in handling them based on the development of educational video and infographic. Method Experience report on the stages of the process of training people to make fabric masks for the population at risk, between March and June 2020, in a city in the interior of São Paulo. Results 1,650 masks were made and distributed to vulnerable population groups from different contexts and tutorial video and infographic were elaborated and released to enable people to make their own masks with resources available at home. Final considerations It was possible to manufacture and distribute masks for the population at risk and develop educational actions to contain the disease, given the advance of confirmed cases and deaths by Covid-19, corroborating the role of nursing in health education.